Mempergiat Pencapaian Kesehatan Jiwa Masyarakat Melalui Pembinaan Kader Kesehatan di Desa Talang Buluh - Kusumawaty, Ira; Yunike, Yunike; Astuti, Ratnaningsih Dewi (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2023)
Long-term treatment of people with mental disorders (ODGJ) can lead to a burden of care, which will be related to the family's decision to pasung. Stigmatization is associated with negative consequences for ODGJ due to disapproval, social rejection, exclusion, and discrimination. Stigmatization can lead to greater potential for confinement in stocks, resulting in the physical and psychological deterioration of the patient. Mental health services in the village through health cadres in the village as an extension of puskesmas services in the community, are thought to be able to help families reduce the burden on families. The development of health cadres is important to be improved through participatory methods that maximize the potential of the community in identifying problems, formulating joint solutions to the process of monitoring, evaluation and follow-up efforts by starting with training and continuing with cadre mentoring. After carrying out the service activities for seven months, there was an increase in the competence of health cadres in detecting mental disorders. Collaboration and coordination between agencies are sought so that the sustainability of activities can be optimized. This service activity is very important considering the increasing number of ODGJ and the importance of the existence of mental health cadres in the village to assist families, so that they do not sink into a state of despair until they decide to commit confinement.